EMP3 as a prognostic biomarker correlates with EMT in GBM - Li, Li; Xia, Siyu; Zhao, Zitong; Deng, Lili; Wang, Hanbing; Yang, Dongbo; Hu, Yizhou; Ji, Jingjing; Huang, Dayong; Xin, Tao (BMC cancer, 2024)
Glioblastoma (GBM) is the most aggressive malignant central nervous system tumor with a poor prognosis.The malignant transformation of glioma cells via epithelial-mesenchymal transition (EMT) has been observed as a main obstacle for glioblastoma treatment. Epithelial membrane protein 3 (EMP3) is significantly associated with the malignancy of GBM and the prognosis of patients. Therefore, exploring the possible mechanisms by which EMP3 promotes the growth of GBM has important implications for the treatment of GBM. We performed enrichment and correlation analysis in 5 single-cell RNA sequencing datasets. Differential expression of EMP3 in gliomas, Kaplan-Meier survival curves, diagnostic accuracy and prognostic prediction were analyzed by bioinformatics in the China Glioma Genome Atlas (CGGA) database and The Cancer Genome Atlas (TCGA) database. EMP3-silenced U87 and U251 cell lines were obtained by transient transfection with siRNA. The effect of EMP3 on glioblastoma proliferation was examined using the CCK-8 assay. Transwell migration assay and wound healing assay were used to assess the effect of EMP3 on glioblastoma migration. Finally, quantitative real-time polymerase chain reaction (qRT-PCR) and western blot were used to detect the mRNA and protein expression levels of EMT-related transcription factors and mesenchymal markers. EMP3 is a EMT associated gene in multiple types of malignant cancer and in high-grade glioblastoma. EMP3 is enriched in high-grade gliomas and isocitrate dehydrogenase (IDH) wild-type gliomas.EMP3 can be used as a specific biomarker for diagnosing glioma patients. It is also an independent prognostic factor for glioma patients' overall survival (OS). In addition, silencing EMP3 reduces the proliferation and migration of glioblastoma cells. Mechanistically, EMP3 enhances the malignant potential of tumor cells by promoting EMT. EMP3 promotes the proliferation and migration of GBM cells, and the mechanism may be related to EMP3 promoting the EMT process in GBM; EMP3 may be an independent prognostic factor in GBM.